REFLEKSI KRITIS DAN ANALISIS STUDI KASUS KEBIJAKAN DALAM SISTEM PENDIDIKAN INDONESIA SERTA REKOMENDASI PERBAIKANNYA - Nurmala Anggun Rahayu; Yudo Handoko (STKIP Subang, 2026)
This study examines critical reflections and case study analyses of policy implementation within the Indonesian education system, focusing on persistent challenges such as policy inconsistency, unequal access to quality education, and gaps between policy design and field execution. The objective of this research is to analyze the effectiveness of selected educational policies and to formulate strategic recommendations for improvement. This study employs a qualitative approach using a literature review and case study method, drawing on recent scholarly sources, government reports, and documented educational practices. The findings indicate that many policies, although conceptually progressive, face significant obstacles in implementation due to limited resources, inadequate teacher training, and weak monitoring systems. Furthermore, disparities between urban and rural educational contexts exacerbate the issue. The study concludes that strengthening policy coherence, improving stakeholder collaboration, and enhancing capacity-building initiatives are essential to achieving sustainable educational reform. These findings provide actionable recommendations aimed at improving policy effectiveness and ensuring equitable education outcomes across Indonesia